A speech act approach to the teaching of functional classification of english sentences in selected secondary schools in Ondo state, Nigeria - Akinkurolere, Susan O.; Ayodele, Victoria O.; Kumuyi, Olubamiji O.; Ogidan, Olajide F.; Ijadimine, Olamide (KIU Interdisciplinary Journal of Humanities and Social Sciences, 2020)
This paper examines the concept of speech act as a pedagogical impetus in the teaching and learning of English Language. The focus on using speech act approach in teaching sentences in English among Secondary Schools attracted this study, with the view to achieving better and effective academic performance among the This paper examines the concept of speech act as a pedagogical impetus in the teaching and learning of English Language. The focus on using speech act approach in teaching sentences in English among Secondary Schools attracted this study, with the view to achieving better and effective academic performance among the Secondary School students. New effective methods are being employed by teachers of English to teach the subject. Hence, the application of a functional approach in consonance with Searle’s classification is crucial in the research. Adequate attention is focused on locutionary, illocutionary and perlocutionary acts, which are relevant in defining the functional classification of the English sentences. The results of the research work form the basis of the discussion and recommendations to provide a further contribution to effective teaching of sentences of English language among Secondary Schools in Ondo State.